Social group membership, burnout, and subjective well‐being in new nurses in the life transition period: A cross‐sectional study - Gaeyoung Kim; Hannah Yu; Eunjung Ryu (Wiley, 2023)
Abstract Aim To assess differences in social group memberships and burnout levels by work tenure among new nurses and identify factors associated with their subjective well‐being. Design A cross‐sectional study. Methods Participants were 356 registered nurses who had fewer than 3 years of work tenure. Data were collected from February-March 2021. Participants' social identity, burnout, and subjective well‐being were assessed using validated questionnaires. STROBE checklist was applied. Results Multiple group membership was positively associated with life satisfaction and positive affect and negatively with burnout. Burnout influenced new nurses' negative effect in their life transition period. To improve new nurses' subjective well‐being, it is essential to focus on their social group membership, encourage participation in group activities, and improve access to sociopsychological resources that can help them take their first steps as professional staff and develop as healthy members of society, which will foster sustainable healthcare systems.